Reflection on Edu-Action of the Prophetic Attributes with Ta’awun Approach - Zainudin, Dolhadi; Mhd. Sarif, Suhaimi; Ismail, Yusof; Yahya, Rohaziah (Meso Publishing, 2021)
This chapter reflects on edu-action practice of ta'awun with Prophetic attributes. The action oriented education enables development with ta’awun innovation. The edu-action drives ta'awun of Prophetic attributes to attain global agenda of sustainability. Sustainability requires partnership, teamwork, and cooperation with every individual regardless of nationality and citizenship. Edu-action enables human well-being is an outcome of integrated attainment of triple bottom line (economic, social, and planet). Education plays essential role to provide the brain, heart and soul to achieve ethical decisions and actions.